Medical Lessons from the 1972 Andes Plane Crash - Carla Crous; Sara Fuentes; Conrado J. Estol; Montse Ibarra; Alexandre González-Rodríguez; Luis Renter; Toni Veres; Roberto Canessa (Wilderness & Environmental Medicine, 2026)
In 1972, a chartered plane carrying rugby players crashed in a remote region of the Andes, leaving 32 survivors exposed to extreme cold, high altitude, and near-total deprivation of food and water. After 72 days, only 16 survived. Two secured rescue after crossing a 16,000-foot peak and a 10-day trek despite severe malnutrition. Although widely known, the medical aspects of this event remain underexamined. We conducted a retrospective descriptive study of the 16 survivors. Data were obtained through interviews with survivors conducted by Roberto Canessa, MD—both a cardiologist and a survivor—along with nurse Willma Kock, who provided immediate postrescue care, and through available medical records. Conditions were classified into 4 domains: trauma triage and multiple trauma; pathologies related to high-altitude exposure; malnutrition and dehydration; and mental health sequelae. Survivors applied effective rudimentary strategies including field triage, conservative trauma management, fracture immobilization, and improvised measures to combat hypothermia and dehydration. High-altitude illness and severe malnutrition were widespread; one case of refeeding syndrome and one traumatic brain injury were documented. None met the DSM-5 criteria for PTSD. This case highlights human resilience, physiological adaptation, and survival under extreme conditions, providing insights into trauma management, environmental medicine, and adaptive behavior in unprecedented scenarios.